BUDAYA URBANITAS DI TIGA PERUMAHAN SEKTOR FORMAL DI KOTA BANDUNG DAN TRANSFORMASI BUDAYA MASYARAKATNYA (Cultural of Urban Society in Three Formal Sector Housing in Bandung and Cultural Transformation Society) - Udjianto Pawitro (Universitas Katolik Soegijapranata, 2015)
One of the important things in discussing the phenomenon of 'urbanity' in the urban communities related to the cultural transformation of society to better prepare the method and behavior in occupied in the urban areas. There are three sub-topics in the research are: (a) a discussion about the conditions of urban society, (b) a discussion of the phenomenon of 'urbanity' in the urban communities, and (c) a discussion of the cultural transformation of the urban community. The research method used was the descriptive exploratory analysis methods that are supported by the data results of the questionnaire and interviewof the residents in the housing areas. The findings of this research are: (a) method or technique of the cultural transformation of the community in the housing areas were observed lasted through the mass media (such as TV, newspapers, magazines, Internet, etc.), (b) the central figure who became driving the change or the transformation of cultural were community leaders informal local